COMMUNITY EMPOWERMENT IN KNOWLEDGE IMPROVEMENT, THE FOOT SOAKING APPLICATION WARM WATER AND FOOT MASSAGE TO HELP RELIEVE SYMPTOMPS OF PREECLAMPSIA - Ika Warisantika; Tridiyawati, Feva (Universitas Airlangga, 2025)
The prevalence of preeclampsia in Indonesia ranges from approximately 3.8% to 8.5%, it causes 24% of people's deaths. So far Pregnant women with preeclampsia have been treated pharmacologically which has adverse effects. The foot by warm water effect mentions a decrease in blood pressure in third-trimester pregnant women who have hypertension in the Kahuripan public health Area. The Related research also shows that providing non-pharmacological therapy in the form of soaking the feet by warm water and massaging the feet over 2 weeks period, it can reduce blood pressure in pregnant women who suffer preeclampsia. The goal of community empowerment is to improve people's knowledge about preeclampsia and to know how to soak non-pharmacologically by warm water and foot massage using health education methods. This therapy has been proven to reduce blood pressure on preeclampsia. The knowledge and skill improvement of people in Kuta Makmur in public health Tirtajaya area. The result of health education is concluded that significant, it is around 83,3% and 93,3% this skills can be done by themselves.